Inventory Of Meat Raw Recipes With Additional Materials In The City Of Padang Panjang - Muthia Khansa; Wirnelis Syarif (Universitas Negeri Padang, 2021)
Rendang is a typical food from West Sumatra. Rendang has 2 criteria, namely wet rendang and dry rendang. This study aims to make an inventory of the beef rendang recipe with additional ingredients including ingredients, spices, tools and processing processes in the city of Padang Panjang. Based on the main background of beef from Padang Panjang, the use and processing process varies by each person, so that various kinds of beef rendang recipes are collected. This type of research is a qualitative descriptive study. Data collection techniques in the form of observation, interviews, and documentation. The data obtained were analyzed by data reduction steps, data presentation and drawing conclusions. Based on the results of the study, 16 recipes from each urban village in Padang Panjang were collected including different ingredients, spices, tools and processing processes.